LITHOGEOCHEMICAL CHARACTERISTICS OF TERRIGENOUS AND VOLCANOGENIC-TERRIGENOUS ROCKS OF THE LATE PALEOZOIC TOCHER FORMATION OF THE BAGDARIN SYNFORM (WESTERN TRANSBAIKALIA) - V. S. Tashlykov; O. R. Minina; Z. L. Motova; N. A. Doronina; S. I. Shtel’makh (Геодинамика и тектонофизика)
The paper presents new data on the composition of Late Paleozoic terrigenous and volcanogenic-terrigenous rocks of the Upper Devonian-Lower Carboniferous Tocher formation of the Bagdarin synform (Western Transbaikalia). The authors consider petrographic and lithogeochemical features of the rocks, and clarify the conditions of depositional environment, source area, and tectonic settings that controlled sedimentogenesis. It has been established that terrigenous rocks of the Tocher formation were formed from decomposing igneous and volcanogenic rocks. The petrographic and lithogeochemical characteristics of the Late Paleozoic sedimentary rocks of the Tocher formation make it possible to classify them as greywacke, arkose, tuffaceous and silt sandstones. The distribution of petrogenic oxides, as well as rare and rare-earth elements, together with the results of petrographic studies of thin sections indicate that mixed (felsic, intermediate, mafic) magmatic rocks were decomposed in the source area. The sediments in the first member of the Tocher formation, were predominantly derived from felsic source rocks, and those in the second and third members – from mafic and intermediate source rocks. The Riphean island-arc volcanics of the Usoy and Burom formations, as well as gabbro-diorites and diorites composing the Shaman basement protrusion of the Bagdarin synform, are presumed to be the main source of clastic material. Another source area at that time could be a magmatic arc, as evidenced by the volcanomictic composition of terrigenous clastic rocks and the presence of pyroclastic rocks. The sedimentary complexes of the Tocher formation were formed in a deepening basin adjacent to the volcanic zone. Sedimentation took place in conditions of the continental slope and its foot, against the background of the growth of paleobasin-border uplifts. These conclusions are in agreement with the previous ideas that the Tocher formation accumulated in the geodynamic environment of an active Andean-type continental margin, concurrently to the formation of the Kydzhimite supra-subduction volcanic zone and the Tocher rear trough-fill graywacke turbidite system at the end of the Late Devonian-beginning of the Early Carboniferous between the Siberian Continent and the Mongol-Okhotsk Ocean.